Association between dietary trace minerals and pelvic inflammatory disease: data from the 2015–2018 National Health and Nutrition Examination Surveys - Hu, Panwei; Zhang, Siming; Li, Haoyuan; Yan, Xiaotong; Zhang, Xiaole; Zhang, Qinhua (Frontiers in Nutrition, 2023)
Objective: Pelvic inflammatory disease (PID) is a prevalent gynecological disorder. Dietary trace minerals play an important role in combating many chronic diseases including PID. However, it is unknown whether dietary trace minerals and PID are related. This study aimed to examine the relationship between dietary trace minerals (copper, iron, selenium, and zinc) and PID. Methods: Data of women participants from the National Health and Nutrition Examination Survey (NHANES) 2015–2018 were enrolled in this cross-sectional investigation. Univariate and multivariate linear regression analyses of the relationship between dietary trace minerals and PID were performed, and restricted cubic spline (RCS) analyses were applied to visualize those relationships. Results: In total, 2,694 women between the ages of 20 and 59 years participated in the two NHANES cycles. In the univariate analyses, a significant negative relationship was identified between PID and dietary copper intake [odds ratio (OR) = 0.40, 95% confidence interval (CI): 0.24–0.67, p < 0.01] but not with iron (OR = 0.96, 95% CI: 0.90–1.03, p = 0.25), selenium (OR = 1.0, 95% CI: 0.99–1.0, p = 0.23), and zinc (OR = 0.94, 95% CI: 0.86–1.03, p = 0.17) intake. Following the adjustment for age and race (model 1), a robust correlation was found between dietary copper intake and PID (OR = 0.23, 95% CI = 0.09–0.61, p < 0.01), as indicated by the fully adjusted model 2 (OR = 0.29, 95% CI = 0.09–0.90, p = 0.03). Simultaneously, a significant trend was found between copper intake and PID across the quintile subgroups (p for trends < 0.05), suggesting a robust relationship. Furthermore, the RCS analysis demonstrated a linear correlation between PID and dietary copper intake (overall p < 0.01, non-linear p = 0.09). Conclusion: Decreased dietary copper intakes are linked to PID. However, additional research is needed to fully investigate this relationship due to the constraints of the study design.